2020
DOI: 10.1159/000506627
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Depression, and Suicidal Ideation amongst Patients with Facial Dermatoses (Acne, Rosacea, Perioral Dermatitis, and Folliculitis) in Lithuania

Abstract: Background/Objective: Skin diseases, especially those with visible manifestation, are considered to cause a major influence on global mental health. Therefore, we determined the prevalence and severity of anxiety, depression, and suicidal ideation in a large sample of patients with facial dermatoses, namely acne, rosacea, folliculitis, and perioral dermatitis. Methods: The mental health of patients with facial dermatoses and respective controls was assessed using the Hospital Anxiety and Depression Scale and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
(31 reference statements)
0
8
1
1
Order By: Relevance
“…In this meta-analysis of the 14 studies [17,18,[25][26][27][28][29][30][31][32][33][34][35][36], we pooled data on 14,134,021 patients with rosacea and 686,447,139 controls (Table 1). Only one study included [ 100,000 patients and three studies included [ 10,000 patients.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In this meta-analysis of the 14 studies [17,18,[25][26][27][28][29][30][31][32][33][34][35][36], we pooled data on 14,134,021 patients with rosacea and 686,447,139 controls (Table 1). Only one study included [ 100,000 patients and three studies included [ 10,000 patients.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A study comparing acne and seborrheic dermatitis found that acne patients had a higher rate and severity of anxiety and depression[ 10 ]. A study in Lithuania comparing acne and rosacea patients aged 18–70 found that acne patients had higher anxiety and rosacea patients had higher depression[ 11 ]. The fact that these studies were completed with a smaller number of patients is a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Thoughts about suicide had 12% of patients. They also had the highest mean score in the anxiety subscale (7,1 ± 0,25) and depression subscale, almost the same as rosacea (5 ± 0,23 acne, 5 ± 0,31 rosacea) (15). The case of suicidal thoughts was also controlled in Altunay et al research, where 213 acne patients from 13 European countries were analyzed using HADS, DLQI and EuroQol 5 scales.…”
Section: Description Of Knowledgementioning
confidence: 95%